Neonatal Systemic Thrombosis: An Updated Overview - Conti, Gea O.; Molinari, Angelo Claudio; Signorelli, Salvatore Santo; Ruggieri, Martino; Grasso, Alfina; Ferrante, Margherita (Current Vascular Pharmacology, 2018)
Thromboembolic disease is a complex disorder with a multifactorial aetiology and a severe outcome. In newborns and children it may be missed or diagnosed late, thus worsening the prognosis. The neonatal disease is different from the disorder affecting older children and adults. However, scant epidemiological data and few randomised clinical trials regarding paediatric patients are available, and treatment recommendations are largely based on adult guidelines. Younger patients then have several decades over which they will suffer from the complications of thrombosis and risk of a new thrombotic episode. Current knowledge about neonatal thromboembolic disease and its prevention is reviewed here along with maternal, foetal, neonatal, pharmacological, environmental, lifestyle and occupational contributing factors. Additional data are urgently needed to improve diagnostic and therapeutic strategies and patient outcomes.
Keywords: thrombophilia